Mechanisms of electrochemical recognition of cations, anions and neutral guest species by redox-active receptor molecules - Beer, P; Gale, P; Chen, G (1999)
This short review highlights the mechanisms involved in electrochemically sensing cationic, anionic and neutral guest species by redox-active receptors and is an update to a previously published review article (P.D. Beer, P.A. Gale, Z. Chen, Adv. Phys. Org. Chem. 31 (1998) 1). Mechanisms of redox-complexation coupling are discussed together with recent examples of redox-responsive molecular receptors from the literature that illustrate them. © 1999 Elsevier Science S.A. All rights reserved.